Sexy Marketing Communication Strategies of Alcoholic Beverages Entrepreneur in Thailand - ขุนพล, เสริมศักดิ์ (Siam Communication Review, 2019)
This research is aimed to survey the strategies of sexy marketing communication for alcohol industries in Thailand since B.E. 2551-2560. There was analyzed from 120 literatures related to marketing communication of 10 popular beverage alcohol marketed in Thailand. The research found that alcoholic beverage operators used all four types of marketing communication tools such as public relations, personal selling, event marketing and sponsorship. The tools that were chosen depended on the rationale of the marketing communication level based on the marketing plan and external factors such as laws and state policies, growth of entertainment and consumer behavior. If any tool has been unappropriated conditions will terminate immediately. A sexy image creation is a combination of sexy images from the social and sexy image of the beverage owner. There are collaboration together between entrepreneurs and consumers. If any sex symbol is overlapping with art or obscene. The decision will make based on the law whether or not to use those sexy signs. The sexy marketing communication doesn’t a measurement for sales successfulness. But it studies about what appeals to consumers turned to the product. It helps operators to continue selling products and marked or put the marketing plan of their product easier.